Cystatin C and Risk of Heart Failure in the Physicians’ Health Study - Djoussé, Luc (2007)
BACKGROUND: Chronic kidney disease is a risk factor for heart failure (HF). Though cystatin C can detect early kidney dysfunction, limited data are available on the association between cystatin C and HF. METHODS: In a prospective nested case-control study design, we examined whether cystatin C is associated with an increased risk of HF in the Physicians’ Health Study and whether such an association is stronger in hypertensive subjects. We selected 220 cases of incident HF and 220 controls, matched on age, year of birth, and time of blood collection. Plasma cystatin C was measured using an immunonephelometry method. We used conditional logistic regression to estimate relative risks. RESULTS: Compared with the lowest tertile, the multivariable adjusted RR (95% CI) for HF was 1.15 (0.69-1.89) and 1.78 (1.01-3.13), for the second and third tertile of cystatin C, respectively. Additional adjustment for systolic blood pressure and history of hypertension attenuated this association [RR: 1.0, 1.23 (0.73-2.09), and 1.61 (0.90-2.88) from the lowest to the highest tertile, respectively]. Furthermore, we observed a 4-fold increased risk of HF in the second and third tertiles of cystatin C among hypertensive individuals and no meaningful effects of cystatin C on HF among non-hypertensive subjects. CONCLUSIONS: Our data demonstrated that higher levels of cystatin C are associated with an increased risk of HF and that such association may be limited to hypertensive individuals. Additional studies are warranted to further examine the relationship between hypertension and cystatin C on the risk of HF.